PENDAMPINGAN SOCIAL BEHAVIOUR TERAPHY DAN CLASSICAL CONDITIONING TERAPHY PADA KOMUNITAS PEDULI ANAK AUTIS - Sangidatus Sholiha; Hadi Pranoto; Al Um Aniswatun Khasanah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
The purpose of this service is to provide support and assistance to children with autism through the implementation of Social Behavior Therapy and Classical Conditioning Therapy. The methods used in implementing this service involve counseling based on counseling service cards, seminars, workshops, and pre-tests and post-tests to measure the effectiveness of the program. The results of the service showed that 85% of parents and caregivers were satisfied with the program, and there was a significant increase in the social skills and adaptive behavior of children with autism. The sustainability of this program is supported by intensive training for caregivers and parents, which ensures consistent application of therapy. This program is expected to be a model for other communities in implementing behavioral therapy for children with autism, creating a more supportive and inclusive environment for them in the future.